Tibet on Fire - Whalen-Bridge, John. author. aut Link
XXIII, 216 p. 6 illus.
Keywords: Using Kenneth Burke's concept of dramatism as a way of exploring multiple motivations in symbolic expression, Tibet on Fire examines the Tibetan self-immolation movement of 2011-2015. The volume asserts that the self-immolation act is an affirmation of Tibetan identity in the face of cultural genocide.